Crimes in Višegrad. The Criminal Responsibility of Milan Lukić before the International Criminal Tribunal for the Former Yugoslavia - Żarna, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
The aim of this article is to present the phenomenon of ethnic cleansing in the eastern part of Bosnia and Herzegovina, using the case of Višegrad as an example. A key role in the extermination of Bosniak Muslims was played by members of Serbian paramilitary organisations and police forces. Their effectiveness in these actions was largely due to their familiarity with the region and the local population. The individual responsible for organising the ethnic cleansing in the Višegrad area was Milan Lukić, the leader of the paramilitary group White Eagles. He was accountable for crimes against humanity targeting Bosniak Muslims, which ultimately led to a complete change in the ethnic structure of the region. This study outlines the entire process of bringing Milan Lukić to justice before the International Criminal Tribunal for the Former Yugoslavia. The article employs a case study method and content analysis.

Celem niniejszego artykułu jest przedstawienie zjawiska czystek etnicznych we wschodniej części Bośni i Hercegowiny na przykładzie Višegradu. Kluczową rolę w eksterminacji boszniackich Muzułmanów odegrali członkowie serbskich organizacji paramilitarnych oraz sił policyjnych. Ich skuteczność w tych działaniach wynikała w dużej mierze ze znajomości regionu i lokalnej społeczności. Osobą odpowiedzialną za organizację czystek etnicznych w rejonie Wyszegradu był Milan Lukić, przywódca grupy paramilitarnej Białe Orły. Ponosił on odpowiedzialność za zbrodnie przeciwko ludzkości wymierzone w boszniackich Muzułmanów, które ostatecznie doprowadziły do całkowitej zmiany struktury etnicznej regionu. Niniejsze opracowanie przedstawia cały proces pociągnięcia Milana Lukića do odpowiedzialności przed Międzynarodowym Trybunałem Karnym dla byłej Jugosławii. W artykule zastosowano metodę studium przypadku oraz analizę treści.
Zbrodnie w Wyszegradzie. Odpowiedzialność karna Milana Lukicia przed Międzynarodowym Trybunałem Karnym dla byłej Jugosławii
Keywords: Bosnia and Herzegovina; Milan Lukić; ethnic cleansing; International Criminal Tribunal for the former Yugoslavia; Višegrads; Bośnia i Hercegowina; czystki etniczne; Międzynarodowy Trybunał Karny dla byłej Jugosławii; Wyszegrad